Some Evidence on the Effect of the Separation of Spending and Taxing Decisions - Winer, Stanley L. (Journal of Political Economy, 1983)
It is often argued that separation of public spending and taxing decisions engenders in the voter overoptimistic hopes that someone else will bear the cost of public services, thereby inducing an increase in the size of government. But are perceived tax prices systematically and persistently reduced by separation? Although in stock markets all agents' expectations may be unbiased, they may or may not be unbiased in political markets. This paper analyzes the separation created in federal states when the central government finances local expenditures. Evidence from a dynamic decisive-voter model is presented that indicates that the separation introduced by federal grants to Canadian provinces did in fact reduce the perceived tax price of provincial public services and raise provincial expenditures. The results suggest also that the effect of separation diminished over time.